Infusing Neuroscience into Teacher Professional Development - Dubinsky, Janet M (Educ Res, 2013)
Bruer (1997) advocated connecting neuroscience and education indirectly through the intermediate discipline of psychology. We argue for a parallel route: the neurobiology of learning, and in particular the core concept of plasticity, have the potential to directly transform teacher preparation and professional development, and ultimately to affect how students think about their own learning. We present a case study of how the core concepts of neuroscience can be brought to in-service teachers – the BrainU workshops. We then discuss how neuroscience can be meaningfully integrated into pre-service teacher preparation, focusing on institutional and cultural barriers.